Peran Internship Participant dalam Meningkatkan Perencanaan dan Pengembangan Karir Mahasiswa - Nopitaria Windika; Fien Zulfikarijah; Siti Nurhasanah (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study is a type of qualitative descriptive research with the aim to determine the role of internship participants in improving student career planning and development. The sample in this study consisted of 30 informants but there were only 7 informants who were selected because they could represent the answers of all informants with social situations that showed that students of the University of Muhammadiyah Malang class of 2018 had begun to feel confused in determining their future career. This study suggests that careful career preparation should be really focused on supporting desired career prospects. The data collection process in this study was carried out by distributing questionnaires in the form of interview links to informants, namely, students of the University of Muhammadiyah Malang class of 2018 who have participated in the internship program. Data analysis techniques conducted in this study consist of data collection, data reduction, data presentation and conclusion. The results of this study indicate that the internship program must be done by students to learn and understand about the world of work. In addition, internship activities also have benefits to improve future career planning and development